Rising - Ludwig, Sidura (Candlewick Press, 2024)
"Melt into the nooks and crannies of this book's unhurried pages, offering a place to rest and a pregnant pause for counting your many blessings--current and imminent! Here, a child and a mother measure, mix, knead, shape, and tuck their dough under a towel like a sleeping baby. Then, as they do every week, they wait while their dough rises, soon to be baked and gratefully shared at a Shabbat gathering with loved ones. Author Sidura Ludwig's poetic narration captures the experience of a Jewish family as they make challah--a lesson in patience, slowing down, faith, and family. Illustrator Sophia Vincent Guy brings light and warmth to the scene, from a sun-bleached, gossamer curtain to the rising steam from the bread, all rendered in delicate, decorative patterns. Whatever their background, readers will be happy to find the author's go-to recipe for challah at the end, along with a glossary and an author's note describing the personal meaning of her family's weekly ritual"--Publisher's website.